Nutritional status of primary school children of a private school in Hanoi, 2024y - Nguyen , Thuy Duong; Nguyen, Xuan Tien Duc; Nguyen, Thi Thuy; Nguyen , Xuan Ninh (Tạp chí Y học Việt Nam, 2025)
Objective: To assess the nutritional status of primary school children, a private school NS. Hoang Mai district, in Hanoi city at the beginning of the 2024-2025 school year. Subject & Methods: A cross-sectional study was conducted among 1675 school children aged 6-10yrs old (928 boys and 747 girls), from grade 1 to 5. The weight and height were measured according to the standardised methods, then nutritional status was assessed by using WHO 2007 standards. Results: The global prevalence of overweight and obesity (Over/Obes) was 62.9% (obesity 18.9%; overweight 44%), this rate was significantly higher (p<0.001) in boys (78.2% /26.9%) than that in girls (44%/9.1%). The rate of stunting was 0,5%, and wasting was 2,1%. Conclusion: The prevalence of Over/Obes among primary school children, private NS. Hoang Mai school, urban Hanoi city is belong to very high levels. Future studies should be expanded to more private schools, and focus on risk factors to provide appropriate methods to control the obesity in this population.